A Survey on Data Mining Techniques Applied on Cardiovascular Diseases and Cancer, Diagnosis and Prognosis - Kamath, D; Ajith, A; Pujari, K; Kumari, P M.K (International Journal of Computer Sciences and Engineering, 2025)
There has been an exponential growth in the number of cardiovascular diseases and cancer in the present world due to unfavorable environmental factors, faulty food, stress and erroneous lifestyle. These two account for a majority of deaths worldwide. Early detection and prevention plays a remarkable role in preventing deaths. It is not an easy task for medical practitioners to instantly come to a conclusive diagnosis. Hence we can resort to data mining techniques to extract occult, foreseeable information that can be acted upon the large set of medical data. In this survey, we have presented an overview on the symptoms, their aggravating factors in various cardiac illnesses and cancer. We have also enlisted, discussed and analyzed data mining techniques such as Decision Tree, Neural Networks, and Naïve Bayes etc. This paper summarizes various review and technical journals on cardiovascular disease and cancer diagnosis and prognosis